2001
DOI: 10.1002/jlcr.2580440122
|View full text |Cite
|
Sign up to set email alerts
|

Charaterization of Tc‐99m‐tricarbonyl complexes as transport substrates of the multidrug resistance (MDR1) P‐glycoprotein

Abstract: One of the best characterized mechanisms of drug resistance in human tumors is overexpression of the multidrug resistance (MDR1) P‐glycoprotein (Pgp). Pgp functions as an energy‐dependent extrusion pump that efficiently transports drugs out of tumor cells and has thus been an attractive target for improving cancer therapies (1). Lipophilic cationic radiopharmaceuticals, such as 99mTc‐sestamibi and 99mTc‐tetrofosmin, have been validated as transport substrates for Pgp in a variety of multidrug resistant human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Dyszlewski also reported it as a transport substrate of the multidrug resistance Pglycoprotein. 6 Control experiments of were carried out in mice 4 and dogs 7 earlier, in which 99m Tc-CO-MIBI showed to be a promising myocardial perfusion-imaging agent with good myocardial uptake and fast liver washout. Subsequently, we found that 99m Tc-CO-MIBI was a mixture with two main components in different reaction conditions whose biodistribution results were distinctively different.…”
Section: Introductionmentioning
confidence: 99%
“…Dyszlewski also reported it as a transport substrate of the multidrug resistance Pglycoprotein. 6 Control experiments of were carried out in mice 4 and dogs 7 earlier, in which 99m Tc-CO-MIBI showed to be a promising myocardial perfusion-imaging agent with good myocardial uptake and fast liver washout. Subsequently, we found that 99m Tc-CO-MIBI was a mixture with two main components in different reaction conditions whose biodistribution results were distinctively different.…”
Section: Introductionmentioning
confidence: 99%